PENGARUH PUPUK NPK DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL KACANG HIJAU (Vigna radiata L.) - N, Yulia Khairunnisa; Kadekoh, Idrianto; Made, Usman (Fakultas Pertanian, Universitas Tadulako, 2024)
Mung beans are a plant belonging to the legume family (Fabaceae) and have many benefits in daily life as a source of food with high vegetable protein. One of the problems in increasing the growth and yield of mung bean plants is low soil fertility. Increasing soil fertility can be done through the application of inorganic and organic fertilizers. This research aims to examine the effect of NPK and liquid organic fertilizer (POC) on the growth and yield of mung bean plants. The research was carried out in Loru Village Land, Biromaru District, Sigi Regency, Central Sulawesi Province. The research period starts from January to April 2022. This research used a factorial Randomized Block Design consisting of two factors. The first factor is NPK Fertilizer with 3 levels, namely N0= Without NPK, N1= 150 kg/ha, N2= 300 kg/ha. The second factor is the Ecofarming POC doses consisting of three levels, namely: without fertilizer, E1= 3.5 l/ha, E2= 7 l/ha. Each treatment was repeated 3 times to obtain 27 plot units. The results showed that there was an interaction between NPK and POC on the number of leaves, giving 7 l/ha POC without NPK produced the highest number of leaves. Application of 150 kg/ha NPK independently produced the highest number of seeds per pod, yield per plot and yield per hectare of mung bean. POC Eco farming 7 l/ha independently produces the highest number of leaves, number of pods in clusters, number of seeds per pod, yield per plot, and yield per hectare of green bean plants.